'Water dripping on a stone': a feasibility study of a healthy weight management conversation approach in routine general practice consultations. (13th November 2020) - Hilder, Jo; Gray, Lesley; Stubbe, Maria; Duncan, Sarah; Dowell, Anthony C
Abstract: Background: Primary health care has an important role to play in the management of weight and yet discussions of healthy weight management do not occur optimally, indicating a need for simple tools and training in brief weight counselling. The 'FABS' approach (focusing on four topic areas: Food, Activity, Behaviour and Support) was developed to address this. Objectives: To explore the feasibility of the 'FABS' approach within routine general practice consultations and its effectiveness in facilitating healthy weight conversations. Method: The FABS approach was run for a trial period in five New Zealand general practices. The approach entailed staff training, the addition to the practice patient management system of a template outlining potential topics for discussion and a patient handout. GPs were asked to use the approach with any adult patient with a body mass index of over 28 kg/m 2 . A descriptive analysis of anonymized quantitative practice data was conducted, with limited qualitative data from an online clinician questionnaire and interviews with GPs and patients. Results: Over 4 months, the template was opened 862 times by 27 clinicians in 830 patient consultations. All FABS topics were raised at least once. Physical activity was raised most frequently, followed by two food-related topics. There was variation between practices and between GPs. GPs tended to raise more topics within a single consultation than the training recommended. The limited clinician survey results and patient interviews also indicated positive responses to the approach. Conclusions: It is possible to provide an infrastructure for healthy weight conversation approaches within general practice so that patients receive supportive and consistent messages on a regular basis. General practice is an appropriate setting for this due to the ongoing relationships with patients and team-based approach, but there is a need for effective training and education to ensure appropriate and effectively delivery.